Rational Design and Evaluation of Mammalian Ribonuclease Cytotoxins - Lomax, Jo E. (2012)
Mammalian pancreatic-type ribonucleases (ptRNases) comprise an enzyme family that is remarkably well suited for therapeutic exploitation. ptRNases are robust and prodigious catalysts of RNA cleavage that can naturally access the cytosol. Instilling cytotoxic activity requires endowing them with the ability to evade a cytosolic inhibitor protein while retaining other key attributes. These efforts have informed our understanding of ptRNase-based cytotoxins, as well as the action of protein-based drugs with cytosolic targets. Here, we address the most pressing problems encountered in the design of cytotoxic ptRNases, along with potential solutions. In addition, we describe assays that can be used to evaluate a successful design in vitro, in cellulo, and in vivo. The emerging information validates the continuing development of ptRNases as chemotherapeutic agents.